(untitled) - Gaspar A. Motta-Ramírez; Erika Santiago-González (Anales de Radiología, México, 2024)
Objective: Despite having no clinical implication in cases of small volumes of air within the venous system, the radiologist should be aware that such a phenomenon is common. Raise awareness about the importance of using the injector and injection of the contrast medium (CM) in CT studies. Material and methods: An extensive bibliographic review was carried out in the PubMed database, where recent bibliographic information was inquired using the following keywords: Venous air embolism (VAE), Iatrogenic VAE, CT injector, including original studies, and bibliographic reviews. Results: We describe the technique and different procedures to prevent air bubbles from being injected into the bloodstream after the use of the injector. We show 3 examples of clinical cases in which it is demonstrated VAE. There is an underdiagnosis of such an iatrogenic situation, which implies a total change of attitude. Conclusion: Clinicians should be aware of this risk when ordering imaging with CM and identify clinical findings of VAE which represents a wide range of clinical of manifestations, ranging from an incidental finding in a clinically asymptomatic patient to obstructive shock and circulatory failure. VAE should be suspected whenever patients experience sudden onset respiratory distress following IV CM injection It is necessary to have an established protocol in which the responsible team monitors the CM application technique through the injector, and everything related to it.